Innate and learnt color preferences in the common green-eyed white butterfly (Leptophobia aripa): experimental evidence - Deysi Muñoz-Galicia; Citlalli Castillo-Guevara; Carlos Lara (PeerJ, 2021)
Background Learning abilities help animals modify their behaviors based on experience and innate sensory biases to confront environmental unpredictability. In a food acquisition context, the ability to detect, learn, and switch is fundamental in a wide range of insect species facing the ever-changing availability of their floral rewards. Here, we used an experimental approach to address the innate color preferences and learning abilities of the common green-eyed white butterfly (Leptophobia aripa). Methods In Experiment 1, we conducted innate preference choice-tests to determine whether butterflies had a strong innate color preference and to evaluate whether color preferences differed depending on the array of colors offered. We faced naïve butterflies to artificial flowers of four colors (quadruple choice-test): yellow, pink, white, and red; their choices were assessed. In Experiment 2, we examined the ability of this butterfly species to associate colors with rewards while exploring if the spectral reflectance value of a flower color can slow or accelerate this behavioral response. Butterflies were first trained to be fed from artificial yellow flowers inserted in a feeder. These were later replaced by artificial flowers with a similar (blue) or very different (white) spectral reflectance range. Each preference test comprised a dual-choice test (yellow vs blue, yellow vs white). Results Butterflies showed an innate strong preference for red flowers. Both the number of visits and the time spent probing these flowers were much greater than the pink, white, and yellow color flowers. Butterflies learn to associate colors with sugar rewards. They then learned the newly rewarded colors as quickly and proficiently as if the previously rewarded color was similar in spectral reflectance value; the opposite occurs if the newly rewarded color is very different than the previously rewarded color. Conclusions Our findings suggest that common green-eyed white butterflies have good learning abilities. These capabilities may allow them to respond rapidly to different color stimulus.